?ISOLATIONANDNMR-ASSIGNMENTS OF 19aH-LuPEOL FROME. HELIOSCOPIA LINN (N.O. EUPHORBIACEAE) - Nazir, Muhammad; Ahmad, Waqar; Kreiser, Wolfgang (Biological Sciences - PJSIR, 1998)
A triterpenoid resembling lupeol was isolated from the latex of Euphorbia helioscopia Linn. The structure was elucidated by physico-chemical methods and confirmed as 19cxH-lupeol.The generated data have been compared with those of stereoparent lupeol, nepehinol and the previously isolated compound which was erroneously given the same structure.